High prevalence of sexually transmitted infections in pregnant adolescent girls in Tanzania: a multi-community cross-sectional study. (1st April 2015) - Hokororo, Adolfine; Kihunrwa, Albert; Hoekstra, Pytsje; Kalluvya, Samuel E; Changalucha, John M; Fitzgerald, Daniel W; Downs, Jennifer A
Abstract : Background: Limited data document sexually transmitted infections (STIs) among pregnant adolescents in sub-Saharan Africa, where prenatal screening typically includes only HIV and syphilis. Given that HIV incidence in this population is among the world's highest, we sought to assess the prevalence and factors associated with STIs in a population of rural pregnant adolescents in Tanzania. Methods: We enrolled 403 pregnant adolescent girls from 10 antenatal clinics near Mwanza, Tanzania. Girls answered structured interviews about sexual health and risk factors and were tested for six common STIs. Results: 199 girls (49.4%) had at least one STI. Herpes Simplex Virus- Type 2 was most prevalent (139 girls, 34.5%), followed by trichomoniasis (54 girls, 13.4%), chlamydia (46 girls, 11.4%), gonorrhoea (27 girls, 6.7%), syphilis (21 girls, 5.2%) and HIV (30 girls, 4.7%). Of note, 53/199 (26.6%) of girls with laboratory-proven STIs were asymptomatic. On multivariable analysis, the presence of any STI was associated with being in a long-term (as opposed to short-term) relationship (OR=2.6 (1.4 to 4.9) p=0.004), younger age at first sexual debut (OR=0.9 per year (0.8 to 0.99), p=0.034), increasing age difference between the girl and her partner (OR=1.1 (1.0 to 1.1) per year, p=0.03) and history of prior pregnancy (OR=1.6 (1.0 to 2.6), p=0.04). Conclusions: STIs affected half of rural pregnant adolescents in Tanzania. Our work demonstrates the urgent need to incorporate routine STI testing into antenatal care in Tanzania to prevent morbidity and mortality in young girls and their babies. We also identify behavioural and demographic risk factors that can be used to target interventions to those at highest risk.